Grain germination changes the profile of phenolic compounds and benzoxazinoids in wheat: a study on hard and soft cultivars. - BARANZELLI, J. (2023)
Abstract: Pre-harvest sprouting is a frequent problem for wheat culture that can be simulated by laboratory-based germination. Despite reducing baking properties, wheat sprouting has been shown to increase the bioavailability of some nutrients. It was investigated whether wheat cultivars bearing distinct grain texture characteristics (BRS Guaraim, soft vs. BRS Marcante, hard texture) would have different behavior in terms of the changes in phytochemical compounds during germination. Using LC-Q-TOF-MS, higher contents of benzoxazinoids and flavonoids were found in the hard cultivar than in the soft one. Free phytochemicals, mainly benzoxazinoids, increased during germination in both cultivars. Before germination, soft and hard cultivars had a similar profile of matrix-bound phytochemicals, but during germination, these compounds have been shown to decrease only in the hard-texture cultivar, due to decreased levels of phenolic acids (trans-ferulic acid) and flavonoids (apigenin) that were bound to the cell wall through ester-type bonds. These findings confirm the hypothesis that hard and soft wheat cultivars have distinct behavior during germination concerning the changes in phytochemical compounds, namely the matrix-bound compounds. In addition, germination has been shown to remarkably increase the content of benzoxazinoids and the antioxidant capacity, which could bring a health-beneficial appeal for pre-harvested sprouted grains.